The Conservative Party and the extreme right 1945-1975 - Pitchford, Mark (Book collections on Project MUSE., 2011)
Shows how the Conservative Party, realising that its well-documented pre-Second World War connections with the extreme right were now embarrassing, used its bureaucracy to implement a policy of investigating extreme right groups and taking action to minimise their chances of success